Use of optical fibres for multi-parameter monitoring in electrical AC machines - Hind, David Martin; Gerada, C.; Galea, Michael; Borg Bartalo, James; Fabian, Matthias; Sun, Tong; Grattan, Kenneth T.V. (2017)
This paper describes a new approach to multi-parameter monitoring for electrical AC machines. It is demonstrated that speed, torque and temperature can be measured using optical fibres incorporating sensors in the form of fibre Bragg gratings (FBGs) distributed around the machine. One fibre can incorporate several FBGs and hence provide several measurements. Experimental results showing speed, torque, direction of rotation, stator housing vibration and temperature measured using the FBG method are presented and validated against measurements obtained from conventional sensors. The results show that the optical fibre based approach allows multiple parameters to be monitored accurately and simultaneously with only a fraction of the usual monitoring equipment required. Another advantage of the proposed method is the EMI immunity naturally provided by optical solutions. The presented measurement technique can also offer a new alternative approach to sensorless control.